STRUKTUR MODAL PERUSAHAAN-PERUSAHAAN NON KEUANGAN YANG TELAH GO PUBLIC DI BURSA EFEK INDONESIA BERDASARKAN TRADE OFF THEORY - Silalahi, Donalson (Jurnal Manajemen dan Bisnis, 2015)
This study aims, First, to obtain the empirical evidence about the capital structure of non-financial firms in Indonesia Stock Exchange. Second, to obtain the empirical evidence about the impact of capital structure on the value of non-financial firms in Indonesia Stock Exchange. Third, to obtain the empirical evidence about the impact of profitability, size of the firm, growth opportunity, the structure of assets, and the cost of bankruptcy to capital structure of non-financial firms in Indonesia Stock Exchange. To achieve these objectives, conducted research on companies listed on the Indonesia Stock Exchange. Research conducted on 163 companies with the observation period in 2011. All the required data obtained from the Indonesian Capital Market Directory. Furthermore, to explain the determinants of capital structure of the firm to used the t and F test with alpha 10 percent. Based on the results of the study, the conclusions as follows: First, the capital structure of the firm has a negative and significant effect on the value of the firm. Second, there is no optimal capital structure on a non-financial corporations. Third, the size of the firm, the structure of assets, and the cost of bankruptcy have positive and significant effect on the capital structure of the firm. Fourth, profitability and the growth opportunities of the firm does not significantly influence to the capital structure. Fifth, variations in the profitability, size of the firm, growth opportunities, the structure of assets, and the cost of bankruptcy are able to explain the variations of capital structure 10,2 percent. Sixth, the coefficient towards research results influence the profitability and bankruptcy costs the company is not in accordance with the trade-offs theory.